2012
DOI: 10.1590/s1415-43662012001100007
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade temporal da potenciometria e da salinidade em vale aluvial no semiárido de Pernambuco

Abstract: As restrições no uso e na disponibilidade das águas subterrâneas nos aluviões do semiárido nordestino estão diretamente ligadas à sazonalidade e à variabilidade espacial de seus níveis potenciométricos e salinidade. A estabilidade temporal é de grande interesse, por facilitar o monitoramento, possibilitando se obter locais representativos acerca da área em estudo, constituindo-se em uma importante ferramenta para a gestão dos recursos hídricos subterrâneos. Com isto, o objetivo deste trabalho foi identificar á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…The box-plot analysis in Figure 2A exhibits several outliers for groundwater levels. Fontes Júnior et al (2012) confirmed in a previous study the presence of these "outliers" and interference in data dispersion. The driest periods have influenced such on extreme groundwater levels, enhanced by unsaturated drainage processes to the watercourse (KONUKCU; GOWING; ROSE, 2006;MONTENEGRO;.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The box-plot analysis in Figure 2A exhibits several outliers for groundwater levels. Fontes Júnior et al (2012) confirmed in a previous study the presence of these "outliers" and interference in data dispersion. The driest periods have influenced such on extreme groundwater levels, enhanced by unsaturated drainage processes to the watercourse (KONUKCU; GOWING; ROSE, 2006;MONTENEGRO;.…”
Section: Resultssupporting
confidence: 83%
“…To study groundwater temporal variability, twelve years records (2002-2013) were used, from three stable piezometers for water table, and for three "near" stable piezometers for electrical conductivity, according Fontes Júnior et al (2012), as shown in …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measuring point of stable moisture was validated through the analysis of correlation between the mean of the response of the stable point and the mean of the other monitored points, as applied by Souza et al (2011) andFontes Júnior et al (2012).…”
Section: Methodsmentioning
confidence: 99%